Exploiting Distal Reactivity of Coumarins: A Rhodium‐Catalyzed Vinylogous Asymmetric Ring‐Opening Reaction. Issue 14 (4th March 2016) - Loh, Charles C. J.; Schmid, Matthias; Peters, Brendan; Fang, Xiang; Lautens, Mark
Abstract: While the utility of vinylogous enolates is well established in the setting of vinylogous aldol, Mannich, and Michael chemistries, literature reports concerning γ‐reactivity are scarce for other reaction classes. Presented herein is an unprecedented example of vinylogous reactivity exemplified by the rhodium‐catalyzed asymmetric ring‐opening reaction of oxabicycles. This strategy also provides a powerful route to incorporate the biologically useful coumarin motif into the hydronapthalene scaffold. Abstract : Gamma style : While γ‐functionalization is well established in the setting of aldol, Mannich, and Michael reactions, γ‐reactivity is scarce in other reaction classes. By using the newly developed vinylogous reactivity involving the release of ring strain in the rhodium‐catalyzed asymmetric ring opening (ARO) the privileged coumarin motif was incorporated into the hydronaphthalene scaffold enantioselectively.